Diversifying the Livelihoods of Small-Scale Fishermen Through Welding Skills Improvement in Kragan District, Rembang - Firmansyah, Hendrix Noviyanto; Al-Janan, Dony Hidayat; Haryadi, Haryadi; Budiman, Febrian Arif (Jurnal Abdimas, 2025)
Karangharjo Village, Kragan Subdistrict, Rembang Regency, is a coastal village where the majority of the population works as traditional fishermen using boats <5 GT. Fish catch productivity is greatly influenced by the seasons, especially during the west wind period when catches drop dramatically to <10 kg/day. The low level of education, with 48.22% of the population only completing primary school, further limits skills and income levels. This situation leads to poverty and livelihood uncertainty. The objective of this community service programme is to develop alternative livelihoods through welding training using Shield Metal Arc Welding (SMAW) techniques as a strategy for diversifying fishermen's livelihoods. The implementation methods include planning, theoretical training, basic welding practice, application of workplace safety standards, and evaluation of participants' skills. The results of the programme show an increase in welding knowledge and skills among the 20 trainees, with some of them having the potential to develop their own welding businesses. This programme contributes to the achievement of the Sustainable Development Goals (SDGs), particularly Goal 8 (Decent Work and Economic Growth) and Goal 17 (Partnerships for the Goals), and supports the strengthening of the local economy through the empowerment of fishermen.